The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.55268/cm.2021.51.27
|View full text |Cite
|
Sign up to set email alerts
|

Hazardous Substances Assessment in Black Sea Biota

Abstract: "The assessment of contaminants in biota is important, not only for biomonitoring of the marine pollution, but also in case of biota used for human consumption there are further implications with respect to public health reasons. Since data on this topic are rather limited in the Black Sea region, activities carried out in the framework of CBC Project “Assessing the vulnerability of the Black Sea marine ecosystem to human pressures” (ANEMONE) contributed at filling knowledge gaps identified for the region. Thu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 4 publications
(7 reference statements)
3
4
1
Order By: Relevance
“…The tissue concentrations of pollutants showed large variations across sampling sites. Low tissue levels of PAHs were measured at all sampling sites, in contrast with the results of previous studies carried out along the Black Sea coast [ 34 , 35 ] and in other seas [ 36 , 37 ].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The tissue concentrations of pollutants showed large variations across sampling sites. Low tissue levels of PAHs were measured at all sampling sites, in contrast with the results of previous studies carried out along the Black Sea coast [ 34 , 35 ] and in other seas [ 36 , 37 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Our study indicated the low-to-moderate HM contamination of mussels at all sampling sites. The results agreed with previous studies carried out along the Romanian Black Sea coast [ 31 , 35 , 41 ]. The HM levels found in our study were similar to those from the Turkish Black Sea coast [ 35 ] and Baltic Sea [ 9 ], higher than those from the southeastern Adriatic Sea [ 1 ], and relatively low compared with the results of other studies carried out in the Gulf of Biscay [ 37 ] and Mediterranean Sea [ 36 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this respect, the use of living organisms to provide information on the quality of aquatic environments is nowadays a widely accepted methodology for assessing contaminants' bioavailability. Information related to the assessment of hazardous substances in biota is rather limited in the Black Sea region, thus in the recent years' activities carried out in the framework of regional or international projects, like FP7 "Policy-oriented marine Environmental Research for the Southern European Seas" (PERSEUS) (Oros et al, 2016), DG ENV "MSFD Guiding Improvements in the Black Sea Integrated Monitoring System" (MISIS) (Coatu et al, 2016) or CBC "Assessing the vulnerability of the Black Sea marine ecosystem to human pressures" (ANEMONE) (Coatu et al, 2020;Oros et al, 2021) aimed to fill knowledge gaps and to help focus future research efforts toward key domains, like the presence of hazardous substances in biota, impact of human pressures upon to the contamination status and trends, and biological effects monitoring.…”
Section: Aims and Backgroundmentioning
confidence: 99%
“…For the Romanian marine waters, data on dangerous substances bioaccumulation in molluscs, fish, macroalgae, etc., are collected in the framework of national monitoring and various national research projects (Oros & Gomoiu, 2012;Coatu et al, 2013;Coatu et al, 2015;Abaza et al, 2016;Coatu et al, 2018;Oros, 2019;Marin et al, 2021), some of the information being also used for the national assessment of the Descriptors 8 and 9 during MSFD reporting cycles: Initial assessment (2012) (Boicenco et al, 2012), and updates of the MSFD Articles 8, 9 and 10 (2018) (Boicenco et al, 2018).…”
Section: Aims and Backgroundmentioning
confidence: 99%